Solar-Thermal Performance of Sparked Stainless Steel-based Solar Absorber under Solar Concentration - Tapsanit Piyawath (E3S Web of Conferences)
Solar absorbers are indispensable components in concentrated solar-thermal (CST) energy systems. Material selection is crucial in optimizing the performance of these systems. Traditional fabrication methods for solar absorbers often rely on chemical processes, which can be both costly and environmentally detrimental. This study presents the first investigation of the solar-thermal performance of a stainless steel absorber fabricated through a non-chemical sparking process in a tip-substrate configuration. Stainless steel, recognized for its cost-effectiveness and high-temperature thermal stability, emerges as a promising candidate for solar absorber applications. The sparked stainless steel exhibited enhanced solar absorptivity of 84.0% and thermal emissivity of 47.3%, representing increases of approximately 33% and 13.7%, respectively, compared to bare stainless steel. Raman spectroscopy and atomic force microscopy confirmed the formation of a random nanotexture of magnetite on the sparked surface, contributing to the improved optical properties. The solar-thermal performance of the sparked stainless steel is maximized at 84.0% when the absorber temperature aligns with the ambient temperature or under conditions of extreme optical concentration. To maintain a solar-thermal performance exceeding 70% at elevated absorber temperatures of 150 °C, 250 °C, 350 °C, and 450 °C, optical concentrations of 5, 13, 28, and 52, respectively, are required.